Pengetahuan dan Sikap Ibu Tentang Pemberian Makanan Bergizi Berkorelasi dengan Perkembangan Kognitif Balita di Desa Bale Busu, Kec. Mutiara Barat, Kab. Pidie - Jamni, Teuku; Suwardi, Suwardi; Novita, Rosi; Oktabina, Rizki Wan; Desiana, Desiana; Hanum, Lathifah (Journal Keperawatan, 2024)
Background: Cases of deviations in the cognitive development of toddlers in Indonesia are still very high. The latest data shows that around 62.02% of toddlers experience this problem. One of the causes is a lack of nutritious food intake and of course this is influenced by the parenting style given by mothers of toddlers, including the mother's level of knowledge and attitudes regarding providing nutritious food. Purpose: To determine the relationship between mothers' knowledge and attitudes about providing nutritious food on the cognitive development of toddlers Methods: This research is a quantitative and cross-sectional design. The study population consists of households with children under five years old and a sample of 45. The search ran from December 2022 to January 2023 in Bale Busu Village. Data analysis using Chi-Square Test includes primary data and secondary data. Results: Based on the research results, it was found that knowledge had a p-value of 0.025, while the attitude p-value was 0.023. Both values are <0.05, so there is a relationship between mother's knowledge and attitudes about providing nutritious food on the cognitive development of toddlers. Conclusion: : There is a relationship between maternal knowledge and attitudes about the provision of nutritious food to early childhood cognitive development.